The assessment and management of lateral ankle ligament injuries - J. De Wilde; D.C. Janse van Rensburg; C.C. Grant; A. Jansen van Rensburg (South African Family Practice)
The assessment and management, as well as the clinical examination, special investigations and treatment of sports-related lateral ankle ligament injuries, are summarised for the general practitioner. Practical advice is discussed, when identifying and diagnosing chronic ankle injuries, and subsequent referral for specialist involvement.